Development and characterisation of polyaniline/polyamide (PANI/PA) fabrics for electromagnetic shielding - USTA, İSMAİL (TAYLOR & FRANCIS LTD, 2015)
In this study, novel conductive fabrics were developed by polymerising of aniline onto the polyamide (PA)-knitted fabrics. The fabric treatment was done by the chemical polymerisation method at 0.5, 0.8 and 1.2 M aniline concentrations. Hydrochloric acid as acidic medium and ammonium per sulphate as oxidant were employed during the polymerisation process. The polyaniline (PANI)-treated PA fabric structures were fully characterised and evaluated in terms of their electromagnetic shielding effectiveness, absorption and reflection characteristics and tensile properties. Additionally, the fabrics were examined by scanning electron microscope (SEM) for the surface morphology and Fourier transform infrared spectroscopy for the chemical functionality. The electromagnetic shielding effectiveness, absorption and reflection characteristics were determined by Network Analyzer with a frequency ranged from 15 to 3000MHz. The electrical characteristics were measured by the two ends method. It has been concluded that the bursting strength values of the treated fabrics reduced when the amount of monomer in the concentrations decreased as compared to the untreated fabrics. It is interesting to note that 1.2M treated fabric had the highest bursting strength values as compared to the other treated fabrics. It was also found that 0.5M concentration of PANI-treated fabric had the lowest surface resistivity due to this it showed the highest conductivity value. Another important finding is that the 0.5M-aniline treated fabric had the highest shielding effectiveness.
Keywords: chemical polymerisation; electromagnetic shielding; polyamide (PA) fabric; polyaniline (PANI); conductive textiles; FREQUENCY-RANGE; COATED FABRICS; FILMS; CONDUCTIVITY; COMPOSITES